Perspectives on the potential of the State of Rio de Janeiro in the beverage production sector and its connection with the field of chemical engineering (Research, Society and Development, 2022)
The beverage sector plays an important role in the Brazilian manufacturing industry, being a major employer in absolute terms and with a wide geographic distribution of production due to the characteristics of the products. In addition, its economic weight is due to the performance of large, small and medium-sized companies that emphasize differentiation as a form of competition. The Beverage Sector in the State of Rio de Janeiro has companies and groups of major brands, as well as a highlight in the area of premium spirits, wineries, craft breweries and non-alcoholic beverages. This work aims to expose, from a panoramic point of view, the potential of the State of Rio de Janeiro, as a region that associates points of cultural and tourist attraction, with its botanical wealth, seeking to emphasize opportunities for technological development. of drinks. Based on the information, it was possible to verify that the state offers the beverage sector a very favorable consumer market, tax benefits laws, structure for Enotourism and the biodiversity of the Atlantic Forest with native fruits that are little known and explored, and with great potential for use. for the formulation and commercialization of new beverages, both alcoholic and non-alcoholic. It is concluded that the evident opportunities identified are inviting factors for new ventures, with the support of development entities and technical support, to be implemented.